2020
DOI: 10.31487/j.scr.2020.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an End Neuroma 6 Months after Capping with a Bioresorbable Polycaprolactone Cap (NEUROCAP®) in a Human Model

Abstract: Various methods have been described in the literature for the treatment of painful end neuromas. One technique involves capping the neuroma with a biological or synthetic material. However, failure of this technique may result from mechanical irritation of the capped nerve. In addition, the physical act of blocking the nerve end is insufficient to prevent further neuroma formation and additional measures need to be taken to halt the regenerative process of the nerve. A new technique of using a bioresorbable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…6 Second, it is known that capped nerve ends may still form neuromas; consequently, the NEUROCAP is not necessarily the ultimate solution. 10 These neuromas may still be painful, as shown in our case, which may be caused by traction on the neuroma or proximal nerve end (so-called mechanosensitivity). 11 Potential disadvantages of TMR, which include size mismatch and the sacrifice of another nerve, should be kept in mind.…”
Section: Lessonsmentioning
confidence: 53%
“…6 Second, it is known that capped nerve ends may still form neuromas; consequently, the NEUROCAP is not necessarily the ultimate solution. 10 These neuromas may still be painful, as shown in our case, which may be caused by traction on the neuroma or proximal nerve end (so-called mechanosensitivity). 11 Potential disadvantages of TMR, which include size mismatch and the sacrifice of another nerve, should be kept in mind.…”
Section: Lessonsmentioning
confidence: 53%
“…A peripheral nerve-end capping device, NEUROCAP (Polyganics, Groningen, Netherland), has been clinically used for the treatment of painful amputation neuroma mainly in Europe since 2017. 14,15,31,32 However, no nerve-end capping device is commercially available in Asia, including Japan. Based on the results of the current study, the Nerbridge colla-gen-coated PGA nerve conduit is a promising nerve-end capping device suitable to treat painful amputation neuroma.…”
Section: Discussionmentioning
confidence: 99%
“…14 George et al also demonstrated that nerve-end capping with NEUROCAP was effective in a case of digital end-neuroma. 32 Parker and Merced-O'Neil presented a 49-year-old female treated by capping of the intermetatarsal neuroma with a processed porcine extracellular matrix wrap, Axoguard (AxoGen, FL), the distal open end of which was sealed using MicroClip (Synovis, AL), and implanting it into the intrinsic muscle belly. 13 Our own work presented the first clinical case of a painful digital amputation neuroma of a 49-year-old female successfully treated by nerve-end capping with a collagen nerve conduit, Renreve (Nipro, Osaka, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…A peripheral nerve-end capping device, NEUROCAP (Polyganics, Groningen, Netherland), has been clinically used for the treatment of painful amputation neuroma mainly in Europe since 2017. 14,15,31,32 However, no nerve-end capping device is commercially available in Asia, including Japan. Based on the results of the current study, the Nerbridge collagen-coated PGA nerve conduit is a promising nerve-end capping device suitable to treat painful amputation neuroma.…”
Section: Discussionmentioning
confidence: 99%